2019
DOI: 10.1002/brb3.1393
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory improvements due to noninvasive stimulation targeting the cortical–hippocampal network: A replication and extension experiment

Abstract: Introduction The distributed cortical network of the human hippocampus is important for episodic memory. In a previous experiment, noninvasive stimulation of the hippocampal‐cortical network applied for five consecutive days improved paired‐associate learning measured after the stimulation regimen via cued recall (Wang et al., Science, 2014, 345, 1054). This finding has not yet been directly replicated. Furthermore, evidence for long‐lasting effects of stimulation on paired‐associate learning was obtained by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
2
28
1
Order By: Relevance
“…The absence of this mid-week task exposure in our study may have attenuated this effect. However, a recent study has successfully replicated these associative memory effects without a mid-week assessment in a sample of 16 healthy adults (Hermiller et al, 2019), suggesting that there may also be other factors influencing our observed outcomes. It is possible that inconsistent effects of rTMS on associative memory may more broadly reflect a variable response to the stimulation.…”
Section: Multi-day Parietal Rtms Associative Memory and Hippocampalmentioning
confidence: 72%
See 4 more Smart Citations
“…The absence of this mid-week task exposure in our study may have attenuated this effect. However, a recent study has successfully replicated these associative memory effects without a mid-week assessment in a sample of 16 healthy adults (Hermiller et al, 2019), suggesting that there may also be other factors influencing our observed outcomes. It is possible that inconsistent effects of rTMS on associative memory may more broadly reflect a variable response to the stimulation.…”
Section: Multi-day Parietal Rtms Associative Memory and Hippocampalmentioning
confidence: 72%
“…retrieving an online link to a questionnaire from a personal email inbox). We acknowledge that this filled delay protocol may differ from past studies (Wang et al, 2014;Hermiller et al, 2019). However, this task minimised the potential for participants to employ mnemonic rehearsal strategies during the delay period, which may have led to biased memory assessments.…”
Section: Associative Memory Task -Face-cued Word Recallmentioning
confidence: 89%
See 3 more Smart Citations